Pengaruh Kemampuan Bahasa Arab Terhadap Pemahaman Makna Ayat Al-Qur’an Mahasiswa Semester 5 Program Studi Pendidikan Bahasa Arab - Bella, Sinta; Hafidz Raudatun Nisa, Mutya; Syafiatul Alawiyah, Iya; Indriana, Dina; Hidayat, Wahyu (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to investigate the effect of Arabic language proficiency on understanding the meaning of Qur'anic verses among 5th semester students of the Arabic Language Education Study Programme. Using quantitative methods with data collection through questionnaires distributed to 20 respondents. The results showed a significant positive correlation, the better the Arabic language skills the deeper the understanding of the Qur'an. Factors such as teaching methods and learning motivation are also influential. This study recommends improving the quality of Arabic language learning to deepen the understanding of the Qur'an among university students. According to the results of the data obtained and it can be concluded that Arabic language ability has a significant positive effect on the total score, with the coefficient B showing a considerable impact. Overall, these results show that Arabic language proficiency has a positive and significant influence on students' understanding of the meaning of the Qur'an.